Coating material and preparation method thereof, coated modified positive electrode material and preparation method thereof, and lithium ion battery

By using Cr modified Co2Mo3N coating material to coat the ternary positive electrode material, the problems of short life and fast capacity decay of the ternary positive electrode material are solved, the circulation and storage performance of lithium-ion batteries are significantly improved, and the structural stability is achieved Improvement of properties and electrochemical properties.

CN119208612AInactive Publication Date: 2024-12-27ZHUJI PAWA NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411697259.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The ternary positive electrode material has a short life and fast capacity decay in lithium-ion batteries. The existing coating modification technology is difficult to effectively suppress structural degradation and intergranular cracks, affecting electrochemical performance.

Method used

Cr modified Co2Mo3N is used as the coating material, and the Cr modified Co2Mo3N coating material is prepared by heating a mixed aqueous solution of cobalt nitrate and ammonium heptamolybdate and stirring in chromium nitrate, and the hydrogen of the matrix material is used. The oxide precursor and the lithium salt are wet mixed and sintered to form a coated and modified positive electrode material.

Benefits of technology

It significantly improves the cycling performance and storage performance of lithium-ion batteries at 4.3V voltage, effectively suppresses structural degradation and intergranular cracks of the positive electrode material, and improves the cycling stability and specific capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208612A_ABST
    Figure CN119208612A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and discloses a Cr-modified Co2Mo3N coating material for the first time. The preparation method comprises the following steps: heating and stirring a mixed aqueous solution of cobalt nitrate and ammonium heptamolybdate, and adjusting the pH value to 5-6; carrying out solid-liquid separation to obtain purple blue precipitate, namely Co2Mo3N; the method comprises the following steps: adding Co2Mo3N into a chromic nitrate aqueous solution, stirring, and carrying out solid-liquid separation to obtain the Cr-modified Co2Mo3N. Secondly, the invention discloses a coated modified positive electrode material, a preparation method thereof and a lithium ion battery. The coating material provided by the invention can effectively inhibit structural degradation and intergranular cracks in the cycle process of the positive electrode material, and after the coated and modified positive electrode material is applied to the lithium ion battery, the cycle performance and storage performance of the battery under 4.3 V voltage can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to the coating modification of positive electrode materials of lithium ion batteries. Background Art

[0002] Lithium-ion battery positive electrode materials include lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, ternary positive electrode materials, etc. Among them, ternary positive electrode materials can well combine the good processing performance of LiCoO2, the high specific capacity of LiNiO2, and the high safety and low cost of LiMnO2, and have the advantages of large discharge capacity, good thermal stability, and stable structure. But at the same time, ternary positive electrode materials also make the battery have the shortcomings of short life and fast capacity decay. In order to improve the electrochemical properties of ternary positive electrode materials, ternary positive electrode materials are usually coated and modified. Generally speaking, coating modification can inhibit irreversible phase change and dissolution of transition metal ions, reduce adverse reactions between positive electrode materials and electrolytes, and reduce the occurrence of side reactions. The selection and application of coating materials are the key research directions of coating modification. Summary of the invention

[0003] The first object of the present invention is to provide a coating material and a method for preparing the same.

[0004] The second object of the present invention is to provide a coated modified positive electrode material and a preparation method thereof.

[0005] A third object of the present invention is to provide a lithium ion battery.

[0006] To achieve the above objectives, the present invention provides the following specific technical solutions.

[0007] Firstly, the present invention provides a coating material, wherein the coating material is Cr-modified Co2Mo3N.

[0008] Secondly, the present invention provides a method for preparing a coating material, comprising: The mixed aqueous solution of cobalt nitrate and ammonium heptamolybdate is heated, stirred, and the pH value is adjusted to 5-6; solid-liquid separation is performed to obtain a purple-blue precipitate, namely Co2Mo3N; Co2Mo3N is added to a chromium nitrate aqueous solution, stirred, and Cr-modified Co2Mo3N is obtained after solid-liquid separation.

[0009] In a further preferred embodiment, the molar ratio of cobalt nitrate to ammonium heptamolybdate in the mixed aqueous solution is 14:3.

[0010] In a further preferred embodiment, the heating temperature is 80-100°C.

[0011] In a further preferred embodiment, the amount of chromium nitrate used is determined based on a mass ratio of Cr to Co2Mo3N of 1-5%:1.

[0012] In a further preferred embodiment, the stirring time is 8-12 hours.

[0013] In addition, the present invention provides a coated modified positive electrode material, wherein the material of the coating layer is Cr-modified Co2Mo3N.

[0014] In a further preferred embodiment, the coated modified positive electrode material comprises a matrix material, and the chemical formula of the matrix material is LiNi x Co y Mn z TM p O2, wherein 0.7≤x<1, 0≤y≤0.3, 0<z≤0.3, x+y+z+p=1, and TM is at least one of Mg, Nb, W, and Zr, preferably Zr.

[0015] In a further preferred embodiment, the molar amount of the Cr-modified Co2Mo3N is 0.1-0.4% of the molar amount of the base material.

[0016] In a further preferred embodiment, the matrix material includes a three-layer structure. From the core to the surface of the matrix material, the molar amount of TM in the first layer structure is 0-1% of the molar amount of the total transition metal ions in the layer; the molar amount of TM in the second layer structure is 0.5~1.5% of the molar amount of the total transition metal ions in the layer; the molar amount of TM in the third layer structure is 1.5~3% of the molar amount of the total transition metal ions in the layer.

[0017] The present invention also provides a method for preparing a coated modified positive electrode material, comprising: mixing a hydroxide precursor of a base material, a coating material and a lithium salt and then sintering the mixture.

[0018] In a further preferred embodiment, the hydroxide precursor of the base material and the coating material are first mixed, and then mixed with the lithium salt. Further preferably, the hydroxide precursor of the base material and the coating material are mixed by wet mixing.

[0019] In a further preferred embodiment, the sintering temperature is 700-1200° C. and the sintering time is 12-24 hours.

[0020] The present invention also provides a lithium ion battery, comprising the above-mentioned coated modified positive electrode material.

[0021] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects: The invention provides a novel coating material for lithium ion battery positive electrode materials.

[0022] The coating material provided by the present invention can effectively inhibit structural degradation and intergranular cracks of the positive electrode material during the cycle process.

[0023] After the coated modified positive electrode material provided by the present invention is applied to a lithium ion battery, the cycle performance and storage performance of the battery at a voltage of 4.3V can be significantly improved.

[0024] The preparation process of the coating material and the coating modification process of the positive electrode material provided by the present invention are very simple, easy to operate, and can be produced on an industrial scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the SEM image of the coated and modified positive electrode material obtained in Example 4.

[0026] Figure 2~Figure 4 This is the battery cycle performance curve. DETAILED DESCRIPTION

[0027] During the research on coating modification of positive electrode materials, especially the coating modification of ternary positive electrode materials, the inventors found that Cr-modified Co2Mo3N can be used as a coating material and has very good application value.

[0028] The study found that cobalt-molybdenum nitride itself has a specific large specific surface area, can provide more active sites, and has good conductivity, which is conducive to fast reaction kinetics. The abundant nitrogen vacancies are conducive to the adsorption and diffusion of lithium ions, enhance the lithium extraction / insertion kinetics in terms of the apparent lithium ion diffusion coefficient, increase the lithium ion transmission rate, and increase the surface activity. Chromium modification helps to increase its specific surface area, improve the structural parameters, enhance the stability of the structure, and effectively inhibit the structural degradation and intergranular cracks during the cycle of the positive electrode material.

[0029] The method for preparing Cr-modified Co2Mo3N comprises: The mixed aqueous solution of cobalt nitrate and ammonium heptamolybdate is heated, stirred, and the pH value is adjusted to 5-6; solid-liquid separation is performed to obtain a purple-blue precipitate, namely Co2Mo3N; Co2Mo3N is added to a chromium nitrate aqueous solution, stirred, and Cr-modified Co2Mo3N is obtained after solid-liquid separation.

[0030] In some embodiments of the present invention, the molar ratio of cobalt nitrate to ammonium heptamolybdate in the mixed aqueous solution is 14:3.

[0031] In some embodiments of the present invention, the heating temperature is 80-100°C.

[0032] In some embodiments of the present invention, the amount of chromium nitrate is determined according to a mass ratio of Cr to Co2Mo3N of 1-5%:1.

[0033] In some embodiments of the present invention, the stirring time is 8-12 hours. By stirring, the purpose of fully mixing the materials can be achieved.

[0034] In addition, some embodiments of the present invention provide a coated modified positive electrode material, wherein the material of the coating layer is Cr-modified Co2Mo3N.

[0035] In some embodiments of the present invention, the coated modified positive electrode material includes a matrix material, and the chemical formula of the matrix material is LiNi x Co y Mn z TM p O2, wherein 0.7≤x<1, 0≤y≤0.3, 0<z≤0.3, x+y+z+p=1, and TM is at least one of Mg, Nb, W, and Zr, preferably Zr.

[0036] In some embodiments of the present invention, the molar amount of the Cr-modified Co2Mo3N is 0.1-0.4% of the molar amount of the base material.

[0037] In some embodiments of the present invention, the matrix material includes a three-layer structure. From the core to the surface of the matrix material, the molar amount of TM in the first layer structure is 0-1% of the molar amount of the total transition metal ions in the layer; the molar amount of TM in the second layer structure is 0.5~1.5% of the molar amount of the total transition metal ions in the layer; the molar amount of TM in the third layer structure is 1.5~3% of the molar amount of the total transition metal ions in the layer.

[0038] In a specific embodiment of the present invention, TM is Zr. The positive electrode material doped with zirconium in a concentration gradient has a narrow particle size distribution and good particle morphology, and can improve the specific capacity and cycle stability of the battery.

[0039] Some embodiments of the present invention also provide a method for preparing a coated and modified positive electrode material, comprising: mixing a hydroxide precursor of a base material, a coating material, and a lithium salt and then sintering the mixture.

[0040] In some embodiments of the present invention, the hydroxide precursor of the base material and the coating material are first mixed, and then mixed with the lithium salt.

[0041] It is further preferred that the hydroxide precursor of the base material and the coating material are mixed by wet mixing. The wet mixing method is: the hydroxide precursor of the base material and the coating material are added to water, stirred, and then the solid-liquid separation is performed, and the obtained solid phase is the hydroxide precursor of the base material and the coating material mixed evenly. Of course, those skilled in the art can also select the solid phase mixing method between the hydroxide precursor of the base material, the coating material, and the lithium salt.

[0042] The hydroxide precursor of the matrix material is prepared by a co-precipitation process.

[0043] In the co-precipitation process, a three-layer hydroxide precursor with different TM distributions can be obtained by adding the amount of transition metal salt and the amount of TM element into the reactor at different time periods.

[0044] In some embodiments of the present invention, the sintering temperature is 700-1200° C.; and the sintering time is 12-24 hours.

[0045] The present invention also provides a lithium ion battery, comprising the above-mentioned coated modified positive electrode material.

[0046] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0047] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0048] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0049] Example 1 Cobalt nitrate and ammonium heptamolybdate were added to water in a molar ratio of 14:3, stirred, heated to 90°C, and the pH value was adjusted to 5.5.

[0050] The purple-blue precipitate was separated by vacuum filtration, rinsed and dried overnight to obtain Co2Mo3N.

[0051] Chromium nitrate nonahydrate was dissolved in water, and Co2Mo3N was added, wherein the mass ratio of Cr to Co2Mo3N was 0.03:1, and the mixture was stirred for 10 hours. After filtering and drying, a chromium-modified Co2Mo3N coated material was obtained.

[0052] Example 2 Cobalt nitrate and ammonium heptamolybdate were added into water in a molar ratio of 14:3, stirred, heated to 100°C, and the pH value was adjusted to maintain at 5.

[0053] The purple-blue precipitate was separated by vacuum filtration, rinsed and dried overnight to obtain Co2Mo3N.

[0054] Chromium nitrate nonahydrate was dissolved in water, and Co2Mo3N was added, wherein the mass ratio of Cr to Co2Mo3N was 0.01:1, and the mixture was stirred for 8 hours. After filtering and drying, a chromium-modified Co2Mo3N coated material was obtained.

[0055] Example 3 Cobalt nitrate and ammonium heptamolybdate were added to water in a molar ratio of 14:3, stirred, heated to 80°C, and the pH value was adjusted to maintain at 6.

[0056] The purple-blue precipitate was separated by vacuum filtration, rinsed and dried overnight to obtain Co2Mo3N.

[0057] Chromium nitrate nonahydrate was dissolved in water, and Co2Mo3N was added, wherein the mass ratio of Cr to Co2Mo3N was 0.05:1, and the mixture was stirred for 9 hours. After filtering and drying, a chromium-modified Co2Mo3N coated material was obtained.

[0058] Comparative Example 1 Compared with Example 1, there is no Cr modification step.

[0059] Cobalt nitrate and ammonium heptamolybdate were added to water in a molar ratio of 14:3, stirred, heated to 90°C, and the pH value was adjusted to 5.5.

[0060] The purple-blue precipitate was separated by vacuum filtration, rinsed and dried overnight to obtain Co2Mo3N.

[0061] Example 4 The Cr-modified Co2Mo3N obtained in Example 1 was mixed with the precursor Ni 0.9 Mn 0.1 (OH)2 was added into a reaction kettle containing water at a molar ratio of 0.003:1 (the molar amount of Cr-modified Co2Mo3N was equal to the molar amount of Co2Mo3N), stirred for 6 h, and then the solid was separated by filtration, washed, and dried.

[0062] The dried material was mixed with lithium hydroxide monohydrate by ball milling at a molar ratio of 1:1.1, and then sintered at 800°C for 18h to obtain a coated modified positive electrode material. The molar amount of the dried material is equivalent to that of the precursor Ni 0.9 Mn 0.1 The molar amount of (OH)2.

[0063] Figure 1 This is the SEM image of the coated and modified positive electrode material obtained in Example 4.

[0064] Example 5 The difference between Example 5 and Example 4 is that the Cr-modified Co2Mo3N is obtained in Example 2.

[0065] Example 6 The difference between Example 6 and Example 4 is that the Cr-modified Co2Mo3N is obtained in Example 3.

[0066] Comparative Example 2 The difference between Comparative Example 2 and Example 4 is that the Cr-modified Co2Mo3N obtained in Example 1 is replaced by the Co2Mo3N obtained in Comparative Example 1.

[0067] Comparative Example 3 The precursor Ni 0.9 Mn 0.1 (OH)2 and lithium hydroxide monohydrate were mixed by ball milling in a molar ratio of 1:1.1, and then sintered at 800°C for 18h to obtain a coated modified positive electrode material.

[0068] Example 7 The Cr-modified Co2Mo3N obtained in Example 1 was mixed with the precursor Ni 0.93 Co 0.02 Mn 0.05 (OH)2 was added into a reaction kettle containing water at a molar ratio of 0.003:1 (the molar amount of Cr-modified Co2Mo3N was equal to the molar amount of Co2Mo3N), stirred for 6 h, and then the solid was separated by filtration, washed, and dried.

[0069] The dried material was mixed with lithium hydroxide monohydrate in a molar ratio of 1:1.1 by ball milling, and then sintered at 820°C for 18h to obtain a coated modified positive electrode material. The molar amount of the dried material is equivalent to that of the precursor Ni 0.93 Co 0.02 Mn 0.05 The molar amount of (OH)2.

[0070] Example 8 The Cr-modified Co2Mo3N obtained in Example 2 was mixed with the precursor Ni 0.95 Co 0.02 Mn 0.03 (OH)2 was added into a reaction kettle containing water at a molar ratio of 0.001:1 (the molar amount of Cr-modified Co2Mo3N was equal to the molar amount of Co2Mo3N), stirred for 4 h, and then the solid was separated by filtration, washed, and dried.

[0071] The dried material was mixed with lithium hydroxide monohydrate in a molar ratio of 1:1.1 by ball milling, and then sintered at 740°C for 15h to obtain a coated modified positive electrode material. The molar amount of the dried material is equivalent to that of the precursor Ni 0.95 Co 0.02 Mn 0.03 The molar amount of (OH)2.

[0072] Example 9 The Cr-modified Co2Mo3N obtained in Example 3 was mixed with the precursor Ni 0.9 Co 0.06 Mn 0.04 (OH)2 was added into a reaction kettle containing water at a molar ratio of 0.004:1 (the molar amount of Cr-modified Co2Mo3N was equal to the molar amount of Co2Mo3N), stirred for 10 h, and then the solid was separated by filtration, washed, and dried.

[0073] The dried material was mixed with lithium hydroxide monohydrate by ball milling at a molar ratio of 1:1.1, and then sintered at 900°C for 20h to obtain a coated modified positive electrode material. The molar amount of the dried material is equivalent to that of the precursor Ni 0.9 Co 0.06 Mn 0.04 The molar amount of (OH)2.

[0074] Example 10 1 mol of precursor material Ni 0.93 Co 0.02 Mn 0.05 (OH)2, 0.003 mol of Cr-modified Co2Mo3N obtained in Example 3, and 1.05 mol of LiOH were ball-milled and mixed, and then sintered at 800°C for 18 hours to obtain a coated modified positive electrode material.

[0075] Embodiment 11 The difference between Example 11 and Example 4 is that the precursor materials are different. Specifically: The precursor material is Ni 0.9 Mn 0.09 Zr 0.01 (OH)2, including three layers of structure from the core to the surface of the precursor material, the molar ratio of Zr / (Ni+Mn) in the first layer structure is 0.5%, the molar ratio of Zr / (Ni+Mn) in the second layer structure is 1%, and the molar ratio of Zr / (Ni+Mn) in the third layer structure is 1.5%; the particle size of the first structure is 2.6~2.9μm, the thickness of the second layer structure is 0.2~0.5μm, and the thickness of the third layer structure is 0.15~0.4μm.

[0076] Example 12 The difference between Example 12 and Example 4 is that the precursor materials are different. Specifically: The precursor material is Ni 0.9 Mn 0.08 Zr 0.02(OH)2, from the core to the surface of the precursor material, includes three layers of structure, the first layer (that is, the core) has a Zr / (Ni+Mn) ratio of 1%, the second layer has a Zr / (Ni+Co+Mn) ratio of 2%, and the third layer has a Zr / (Ni+Co+Mn) ratio of 3%; the particle size of the first structure is 2.6~2.9μm, the thickness of the second layer is 0.2~0.5μm, and the thickness of the third layer is 0.15~0.4μm.

[0077] Comparative Example 4 The difference between Comparative Example 4 and Comparative Example 2 is that: The precursor materials are different. Specifically: The precursor material is Ni 0.9 Mn 0.09 Zr 0.01 (OH)2, from the core to the surface of the precursor material, includes three layers of structure, the ratio of Zr / (Ni+Co+Mn) in the first layer structure is 0.5%, the ratio of Zr / (Ni+Co+Mn) in the second layer structure is 1%, and the ratio of Zr / (Ni+Co+Mn) in the third layer structure is 1.5%; the particle size of the first structure is 2.6~2.9μm, the thickness of the second layer structure is 0.2~0.5μm; the final particle size of the third layer structure is 0.15~0.4μm.

[0078] The positive electrode materials obtained in Examples 4 to 12, Comparative Example 2, Comparative Example 3, and Comparative Example 4 were respectively assembled into batteries in the following manner: the positive electrode material, the binder PVDF, and the conductive agent were mixed in a ratio of 8:1:1, dry-ground for 10 minutes, and then the solvent NMP was added. After stirring evenly with a homogenizer, a positive electrode slurry was obtained, and the positive electrode slurry was evenly coated on an aluminum foil; a metal lithium sheet was used as a negative electrode; a lithium ion secondary electrolyte LB-037 (1M LiPF6in DEC:EC:EMC=1:1:1 Vol%) was used as an electrolyte, and Celgard2325 was used as a separator to assemble into a LIR2032 button battery.

[0079] The electrical properties of the battery were tested in the following manner: in a 25°C constant temperature box, the battery was charged at a constant current of 0.1C to a voltage of 4.3V, then charged at a constant voltage of 0.01C and discharged at 0.1C to 3V, and the cycle was repeated twice. The battery was then charged at a constant current of 0.5C to a voltage of 4.3V, then charged at a constant voltage of 0.05C and discharged at 0.5C to 3V, and the charge and discharge capacity was recorded.

[0080] Test results such as Figure 2-Figure 4 shown.

[0081] from Figure 2It can be seen that the Cr-modified Co2Mo3N coated modified positive electrode material makes the battery have good cycle stability, and in the process of preparing the positive electrode material, the Cr-modified Co2Mo3N is first wet-mixed with the precursor, and then sintered with the lithium salt to obtain the positive electrode material. The performance of the positive electrode material obtained in this way is better than that of the positive electrode material obtained by solid-phase mixing of the hydroxide precursor, Cr-modified Co2Mo3N and the lithium salt and then sintering.

[0082] from Figure 3 It can be seen that the performance of the cathode material modified by simple Co2Mo3N coating is worse than that of the cathode material modified by Cr-modified Co2Mo3N coating.

[0083] from Figure 4 It can be seen that the positive electrode material modified by Cr-modified Co2Mo3N coating makes the battery have better cycle stability. In addition, the concentration gradient of the doped elements in the positive electrode material increases from the core to the surface, and the cycle stability performance of the battery is even better.

[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A coating material, characterized in that: The coating material is Cr-modified Co2Mo3N.

2. A method for preparing a coating material, characterized in that: include: The mixed aqueous solution of cobalt nitrate and ammonium heptamolybdate is heated, stirred, and the pH value is adjusted to 5-6; solid-liquid separation is performed to obtain a purple-blue precipitate, namely Co2Mo3N; Co2Mo3N is added to a chromium nitrate aqueous solution, stirred, and Cr-modified Co2Mo3N is obtained after solid-liquid separation.

3. The preparation method according to claim 2, characterized in that: Include at least one of the following conditions (1) to (4): (1) The molar ratio of cobalt nitrate to ammonium heptamolybdate in the mixed aqueous solution is 14:3; (2) The heating temperature is 80-100°C; (3) The amount of chromium nitrate is determined based on the mass ratio of Cr to Co2Mo3N being 1-5%:1; (4) The stirring time is 8-12 hours.

4. A coated modified positive electrode material, characterized in that: The material of the coating layer is Cr-modified Co2Mo3N.

5. The coated modified positive electrode material according to claim 4, characterized in that: The coated modified positive electrode material includes a base material, the chemical formula of which is LiNi x Co y Mn z TM p O2, wherein 0.7≤x<1, 0≤y≤0.3, 0<z≤0.3, x+y+z+p=1, and TM is at least one of Mg, Nb, W, and Zr.

6. The coated modified positive electrode material according to claim 4 or 5, characterized in that: The molar amount of the Cr-modified Co2Mo3N is 0.1-0.4% of the molar amount of the base material.

7. The coated modified positive electrode material according to claim 5, characterized in that: The matrix material includes a three-layer structure. From the core to the surface of the matrix material, the molar amount of TM in the first layer structure is 0-1% of the molar amount of the total transition metal ions in the layer; the molar amount of TM in the second layer structure is 0.5-1.5% of the molar amount of the total transition metal ions in the layer; and the molar amount of TM in the third layer structure is 1.5-3% of the molar amount of the total transition metal ions in the layer.

8. A method for preparing a coated modified positive electrode material, characterized in that: include: The hydroxide precursor of the positive electrode material, the coating material according to claim 1 or the coating material prepared by the preparation method according to any one of claims 2 to 3, and the lithium salt are mixed and sintered.

9. The preparation method according to claim 8, characterized in that: The hydroxide precursor of the base material and the coating material are first mixed, and then mixed with the lithium salt.

10. A lithium ion battery, characterized in that: It includes the coated and modified positive electrode material according to any one of claims 4 to 7 or the coated and modified positive electrode material prepared by the preparation method according to any one of claims 8 to 9.